Action Naming Test (ANT) 번안 및 국내 성인 적용: 예비연구 - 이옥분(Ok Bun Lee) (언어치료연구, 2017)
목적: Action naming test(Obler & Albert, 1979)는 흑백 선그림으로 이뤄진 행위그림으로 미국 내 건강한 성인과 신경언어장애 환자를 대상으로 실시되는 이름대기 평가의 하나이다. 이 연구에서는 국내 행위 및 동사이름대기 평가도구가 매우 제한적인 상황을 고려하여, 예비적으로 ANT를 사용하여 국내 성인을 대상으로 행위 이름대기 수행력을 알아보고 이 검사어휘들에 대한 친숙도와 임상도구로서의 필요도를 알아보는 데 있다. 방법: 이 연구에서는 ANT 평가어휘를 한국어로 번안 및 검토 후, 의사소통문제가 없는 건강한 성인 20대에서60대에 이르는 111명(여성 64명, 남성 47명)을 대상으로 실시하였다. 대상자들은 평가어휘에 대한 개인적인친숙도와 임상도구로서의 평가 필요도를 5점 평정척도로 실시하였다. 자료처리는 전체 대상자들의 성별, 연령대별, 직업유형, 거주지역 요인별로 집단 간 이름대기 평균값과 표준편차를 구하였으며, 집단 간 차이를 알아보기 위해 일원분산분석을 실시하였다. 그리고 ANT 이름대기 총점과 어휘 친숙도 및 평가 필요도 간의 상관성을 알아보기 위해 피어슨 상관계수와 스피어만 상관계수를 구하였다. 결과: 첫째, 연령이 증가할수록 ANT 총점수는 감소하였다. 특히, 30대의 젊은 성인그룹이 다른 연령대 그룹에 비해 ANT 총점수가 높게 나타났으며, 이 결과는 통계적으로 유의하였다. 그리고 직업유형에 따른 집단 간 총점수와 평가 필요도 요인에서 유의한 차이가 있었다. 전체 대상자들의 어휘 친숙도와 임상적 필요도는 평균 4점대로 나타났다. 둘째, 전체 대상자의 이름대기 총점수와 어휘 친숙도가 약한 수준의 상관성이 있는 것으로 나타났다. 결론: 이 연구에서 행위이름대기 수행력이 연령이 증가할수록 낮아지는 경향을 보였다. 추후 연구에서는 보다 다양한 연령대와 대상자 그리고 어휘의 언어적 조건을 고려한 검토가 지속되어야 할 것이다. Purpose: The action naming test (Obler & Albert, 1979) has used line-drawing of actions to assess the naming ability of healthy and aphasic adults in America. The purpose of this preliminary study aimed to find the naming abilities of Korean adults by using ANT and to know the relation naming ability and word familiarity and needs as clinical tools. Methods: The words in the ANT were translated from English to Korean. One hundred and eleven healthy adults (64 females, 47 males) aged between 20 and 60 years of age participated in the naming task of the ANT. In addition, they were enrolled in a survey to measure the familiarity for each word and the needs level as a clinical tool on a five-point scale. A one-way ANOVA was used for the analysis of difference between groups. Pearson and Spearman Correlation r were utilized to know the relation with total scores of the ANT, word familiarity, and need level as a clinical tool. Results: First, total scores of the ANT decreased with increasing age. The total scores of the ANT in young adults in their 30s were significantly higher than adults in other ages. There was a significant difference in total scores and need level as a clinical tool within groups according to fields of work. In need level and word familiarity, all subjects showed an average of four points. Second, there was a weak correlation between total scores and word familiarity for all adults (Pearson r=.315, Spearman r=.377, p<.01). Conclusions: Young adults performed better than old adults in action naming task. However, considerations should be taken that the adaptations to the Korean language are incomplete. KCI Citation Count: 0